2023
DOI: 10.4236/jssm.2023.161004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Artificial Intelligence on Supply Chain Management Performance

Abstract: Artificial Intelligence (AI) has the potential to revolutionize various aspects of business operations. AI can be used to analyze data and make predictions about demand, optimize logistics and transportation routes, and identify inefficiencies in the supply chain. This can lead to improved responsiveness to changes in demand, reduced lead times, and lower costs. This paper reviews and analyzes the applications of AI in supply chain management (SCM) using the Scopus database. The objective is to address the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The output of the scoping review in this study showed the usage of available existing technology in current SCM processes is essential, as it has numerous benefits in diverse fields under SC, such as the ability to forecast customers' future demand, logistics hub, distribution and transportation, marketing, planning production system, and taking inventory in a warehouse. Also, the research further showed that technology can enhance SCM from the standpoint of Agile and Lean by improving the organization's potential to adapt and adjust to the labor market, cutting waste in production, and improving customer happiness and teamwork (Mohsen, 2023). Despite the several possible advantages of technology application in SCM, it is vital to indicate that integrating technology into SCM involves some challenges.…”
Section: Discussionmentioning
confidence: 99%

An evaluation of current technology in supply chain management

Raymond Yaw Sitsofe Agidi,
Chinedu Joseph Ezeh,
Olanrewaju Adebola Lawal
et al. 2024
Int. J. Sci. Res. Arch.
“…The output of the scoping review in this study showed the usage of available existing technology in current SCM processes is essential, as it has numerous benefits in diverse fields under SC, such as the ability to forecast customers' future demand, logistics hub, distribution and transportation, marketing, planning production system, and taking inventory in a warehouse. Also, the research further showed that technology can enhance SCM from the standpoint of Agile and Lean by improving the organization's potential to adapt and adjust to the labor market, cutting waste in production, and improving customer happiness and teamwork (Mohsen, 2023). Despite the several possible advantages of technology application in SCM, it is vital to indicate that integrating technology into SCM involves some challenges.…”
Section: Discussionmentioning
confidence: 99%

An evaluation of current technology in supply chain management

Raymond Yaw Sitsofe Agidi,
Chinedu Joseph Ezeh,
Olanrewaju Adebola Lawal
et al. 2024
Int. J. Sci. Res. Arch.
“…The study follows the methodology used in the prior studies (Mohsen, 2023) and (Mediavilla et al, 2022), which collect secondary data from top and famous publishers.…”
Section: Methodsmentioning
confidence: 99%
“…Improving supply chain performance is critical to business success. (Mohsen, 2023) stated that AI applications may aid in reducing inventory costs, improving warehouse efficiency, reducing lead times, and lowering costs. Previous research has demonstrated the practical importance of AI-based techniques for demand forecasting.…”
Section: Impact Of Ai Methods On Supply Chain Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Yapay zeka, kurumsal operasyonların birçok yönünü derinden dönüştürme kapasitesine sahiptir. Yapay zeka, verileri analiz etmek ve talep tahminleri oluşturmak, lojistik ve nakliye rotalarını optimize etmek ve tedarik zincirindeki verimsizlikleri tespit etmek için kullanılabilir (Mohsen, 2023). Böylece mevcut sorunların çözümü hızlanabilir.…”
Section: Tedarik Zincirinin Optimizasyonuunclassified